2004
DOI: 10.1158/0008-5472.can-03-2025
|View full text |Cite
|
Sign up to set email alerts
|

Kallikrein 4 is a Predominantly Nuclear Protein and Is Overexpressed in Prostate Cancer

Abstract: Kallikreins (KLKs) are highly conserved serine proteases that play key roles in a variety of physiological and pathological processes. KLKs are secreted proteins that have extracellular substrates and function. For example, prostate-specific antigen (or KLK3) is a secreted protein that is widely used as a diagnostic marker for prostate cancer. KLK4 is a recently identified member of the kallikrein family that is regulated by androgens and is highly specific to prostate for expression. Here, we show that the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
84
2
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 35 publications
14
84
2
4
Order By: Relevance
“…In an attempt to confirm their results, we did assess MMP20 and KLK4 expression in ALCs by use of quantitative real-time PCR, but we did not reach the cycle thresholds for MMP20 and KLK4 transcripts by our 35-cycle cutoff point. This is why we used the human prostate carcinoma cell line LNCaP, which expresses KLK4 (Xi et al, 2004), for our TGF-β1/KLK4 expression-level studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an attempt to confirm their results, we did assess MMP20 and KLK4 expression in ALCs by use of quantitative real-time PCR, but we did not reach the cycle thresholds for MMP20 and KLK4 transcripts by our 35-cycle cutoff point. This is why we used the human prostate carcinoma cell line LNCaP, which expresses KLK4 (Xi et al, 2004), for our TGF-β1/KLK4 expression-level studies.…”
Section: Discussionmentioning
confidence: 99%
“…The human prostate carcinoma cell line (LNCaP) was purchased from ATCC (Manassas, VA, USA) because it expresses KLK4 (Xi et al, 2004). These cells were cultured at pH 7.4 in modified (ATCC) RPMI1640 medium (Invitrogen) supplemented with 10% fetal bovine serum.…”
Section: Cell Culturementioning
confidence: 99%
“…Assessment of KLK protein dysregulation in ovarian cancer was compiled from the results of 17 studies (Dong et al, 2001;Luo et al, 2001Luo et al, , 2003Tanimoto et al, 2001;Hoffman et al, 2002;Yousef et al, , 2003bBorgono et al, 2003;Diamandis et al, 2003;Ni et al, 2004;Scorilas et al, 2004;Xi et al, 2004;Prezas et al, 2006;Shan et al, 2007;Bayani et al, 2008;Shaw and Diamandis, 2008). Chromosomal aberration in ovarian cancer was extracted from the Progenetix comparative genomic hybridisation database available as of January 2009 (Baudis and Cleary, 2001).…”
Section: Bioinformatic Analysismentioning
confidence: 99%
“…Diagnostic tests that combine serum KLK2 with total PSA (Recker et al , 2000 ) and free PSA (Stephan et al , 2006 ) have improved the sensitivity and specifi city of detection. In addition, KLK4 mRNA was shown to be upregulated in PCa tissues (Yousef et al , 1999 ;Obiezu et al , 2002 ;Xi et al , 2004 ;Avgeris et al , 2011 ) and may play a role in epithelial to mesenchymal transition (Veveris -Lowe et al, 2005 ). On the other hand, studies showed that KLK10, a potential tumor suppressor, was downregulated in more aggressive PCa s (Luo and Diamandis , 2000 ).…”
Section: Introductionmentioning
confidence: 99%